Expression of Arabidopsis SHN1 in Indian Mulberry (Morus indica L.) Increases Leaf Surface Wax Content and Reduces Post-harvest Water Loss - Sajeevan, R. S.; Nataraja, Karaba N.; Shivashankara, K. S.; Pallavi, N.; Gurumurthy, D. S.; Shivanna, M. B. (Frontiers in Plant Science, 2017)
Mulberry (Morus species) leaf is the sole food for monophagus silkworms, Bombyx mori L. Abiotic stresses such as drought, salinity, and high temperature, significantly decrease mulberry productivity and post-harvest water loss from leaves influence silkworm growth and cocoon yield. Leaf surface properties regulate direct water loss through the cuticular layer. Leaf surface waxes, contribute for cuticluar resistance and protect mesophyll cells from desiccation. In this study we attempted to overexpress AtSHN1, a transcription factor associated with epicuticular wax biosynthesis to increase leaf surface wax load in mulberry. Agrobacterium mediated in vitro transformation was carried out using hypocotyl and cotyledonary explants of Indian mulberry (cv. M5). Mulberry transgenic plants expressing AtSHN1 displayed dark green shiny appearance with increased leaf surface wax content. Scanning electron microscopy (SEM) and gas chromatograph–mass spectrometry (GC-MS) analysis showed change in pattern of surface wax deposition and significant change in wax composition in AtSHN1 overexpressors. Increased wax content altered leaf surface properties as there was significant difference in water droplet contact angle and diameter between transgenic and wild type plants. The transgenic plants showed significant improvement in leaf moisture retention capacity even five hours after harvest and there was slow degradation of total buffer soluble protein in detached leaves compared to wildtype. Silkworm bioassay did not indicate any undesirable effects on larval growth and cocoon yield. This study demonstrated that expression of AtSHN1, can increase surface wax load and reduce the post-harvest water loss in mulberry.